Electro-conductive Palmyra Fibers By In Situ Polymerization of Pyrrole - Arobindo Chatterjee; B. Manivannan; Subhankar Maity (Journal of Natural Fibers, 2017)
Palmyra (Borassus flabellifer L.) is one of the natural fruit fibers that are available in plenty. This fiber has many advantages, such as biodegradability, renewability, low density, and low cost, which offer greater opportunities to develop new applications. Imparting electrical conductivity to this fiber may open up avenues for various novel applications. In the present study, Palmyra fibers are made electro-conductive by in situ chemical polymerization of pyrrole with FeCl3 oxidant and PTSA dopant. Prepared electro-conductive fibers show average electrical resistivity 2.96 kΩ cm−1. A positive correlation is found between fiber-length and electrical resistance, whereas a negative correlation is found in between fiber-diameter and electrical resistance. FTIR study is conducted to understand the chemical interaction between lingo-cellulose and polypyrrole. Tensile properties and thermal degradation behavior of the prepared electro-conductive fibers are evaluated, and significant deterioration of both tensile properties and thermal stability is observed. Due to this reason, these electro-conductive fibers are unsuitable for mechanical processing and high-tech applications. But the response of these fibers in different pH solution is investigated, and their possible application as a pH sensor has been explored.